Adaptive Classroom Berbasis IoT, Manajemen Penggunaan Air Conditioner Secara Otomatis: Adaptive Classroom Based of IoT, Automatic Usage Management of Air Conditioner - Muhamad Pahrurrozi; I Gde Putu Wirarama Wedashwara W; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
Temperature and humidity are one of the comfort factors. According to the SNI standard, the comfortable temperature range is at 20.5°C-27.1°C. If the temperature is above 27.1°C, an Air Conditioner (AC) is needed to get the effective thermal comfort. AC installed in each PSTI FT UNRAM classroom is operated manually. This research implements Internet of Things (IoT) for automatic AC usage management. This IoT device is made using PIR sensor and DHT22 sensor, the MQTT protocol for data communication between the IoT device and the web system. Based on the testing scenario for the classroom containing students and the empty classroom that has been done, the IoT device is able to manage the AC usage automatically, so that the classroom can be called adaptive classroom. From the MOS testing that has been done, a value of 4.57 from a scale of 5, the system is feasible to use.